2006
DOI: 10.1159/000092053
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of International Prostate Symptom Scores and Urodynamic Parameters in Men and Women with Lower Urinary Tract Symptoms

Abstract: Background: We compared urinary symptoms and urodynamic parameters in men and women with lower urinary tract symptoms. Methods: A total of 164 individuals (76 men and 88 women) were rated according to the International Prostate Symptom Score and underwent a detailed urodynamic investigation. Patients were stratified by age into 2 groups, namely, those <50 years (the younger group) and those >50 years (the elderly group). Results: In the elderly group, scores of voiding symptoms for men were higher than those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The contributing pathophysiologies include a wide differential: storage overactivity, voiding underactivity, outlet obstruction, fluid balance problems, “functional” incontinence of the elderly, and/or sphincter weakness. Conflicting data exists in the literature as to whether symptom questionnaire scores correlate to urodynamic findings such as detrusor overactivity, maximum detrusor pressures, cystometric capacity and stress incontinence [9-12]. …”
Section: Questionnaire Evaluation Of Oabmentioning
confidence: 99%
“…The contributing pathophysiologies include a wide differential: storage overactivity, voiding underactivity, outlet obstruction, fluid balance problems, “functional” incontinence of the elderly, and/or sphincter weakness. Conflicting data exists in the literature as to whether symptom questionnaire scores correlate to urodynamic findings such as detrusor overactivity, maximum detrusor pressures, cystometric capacity and stress incontinence [9-12]. …”
Section: Questionnaire Evaluation Of Oabmentioning
confidence: 99%
“…On and Ku compared the IPSS and urodynamic parameters and reported that the mean value of IPSS-VS was 10.3 ± 1.0 in women <50 years and 8.6 ± 0.8 in women >50 years. [ 18 ] Carlson et al evaluated women with LUTS with a urodynamic study and reported that high voiding symptoms scores (12.3 points) may increase the suspicion of voiding abnormalities in women with abnormalities on the pressure flow study, although the symptoms were not specific. [ 19 ] In our study, the cutoff value for IPSS-VS was found to be nine.…”
Section: Discussionmentioning
confidence: 99%